Application of Fuzzy Delphi Technique to Determine the Elements in Sketch Module for Design and Technology Students - Anisah Ahmad, Nor; Che Ros, Ridzwan; Kamis, Arasinah; Raja Abdullah, Raja Nazim; Abdullah, Norhafillah (International Journal of Psychosocial Rehabilitation, 2019)
Sketching skills can enhance student’s creativity. However, it should be guided by well-planned and systematic methods. The sketch module is one of the methods that can help students to master the sketch skills in stages. This study aims to identify the elements required in developing the Sketch module for sketching topics in design and technology subjects. In this study, a quantitative method had been implemented by using the fuzzy Delphi method (FDM). A questionnaire consisting of 9 elements was given to the 13 experts selected by the purposive sampling method. The findings showed that the expert agreement on all 9 items exceeds 75% and all defuzzification values for each item exceed the value of α-cut = 0.5. This means that all of these elements are accepted by the experts. Through the instrumentality of the module, it is hoped to enhance the sketching skills among students and will help them to be more confident in creating new things. Further study of the findings will be continued in the development phase of the Sketch Module